Low cost one time password authentication system - Dias, Julio Da Silva (2009)
© 2009 IADIS.Client authentication process through public networks reveals several problems not allowing applications to be safely accessed by the users. We propose and implemented a low cost authentication method based on challenge-response protocol with a one-time password calculated through the uses of quadratic functions. This authentication method can be used by financial institutions or other web based applications in to order to achieve secure authentication. The current implementations are analyzed, as well as evolutions proposals for this model so that the necessary security requirements are fulfilled.